2016
DOI: 10.1086/688235
|View full text |Cite
|
Sign up to set email alerts
|

Changes to Intestinal Transport Physiology and Carbonate Production at Various CO2Levels in a Marine Teleost, the Gulf Toadfish (Opsanus beta)

Abstract: Most marine teleosts defend blood pH during high CO2 exposure by sustaining elevated levels of HCO3(-) in body fluids. In contrast to the gill, where measures are taken to achieve net base retention, elevated CO2 leads to base loss in the intestine of marine teleosts studied to date. This loss is thought to occur through transport pathways previously demonstrated to be involved with routine osmoregulation in marine teleosts. The main objective of this study was to characterize the intestinal transport physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
2
12
1
Order By: Relevance
“…The demand to secrete HCO 3 − in the intestine to maintain water balance is well-conserved across marine teleosts 30 . Increased intestinal HCO 3 − secretion with CO 2 exposure as reported here has also been demonstrated at higher CO 2 levels in the plainfin midshipmen (~50,000 μatm CO 2 ) 46 , in the toadfish (5000–20,000 μatm CO 2 ) 23 , and suggested from gene expression and/or protein assays in the Japanese ricefish (7000 μatm CO 2 ) 34 and the Atlantic cod (1,200 and 2,200 μatm CO 2 ) 41 . These studies suggest that increased intestinal HCO 3 − secretion and metabolic demand during CO 2 exposure could be a ubiquitous response to elevated CO 2 throughout marine bony fishes.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The demand to secrete HCO 3 − in the intestine to maintain water balance is well-conserved across marine teleosts 30 . Increased intestinal HCO 3 − secretion with CO 2 exposure as reported here has also been demonstrated at higher CO 2 levels in the plainfin midshipmen (~50,000 μatm CO 2 ) 46 , in the toadfish (5000–20,000 μatm CO 2 ) 23 , and suggested from gene expression and/or protein assays in the Japanese ricefish (7000 μatm CO 2 ) 34 and the Atlantic cod (1,200 and 2,200 μatm CO 2 ) 41 . These studies suggest that increased intestinal HCO 3 − secretion and metabolic demand during CO 2 exposure could be a ubiquitous response to elevated CO 2 throughout marine bony fishes.…”
Section: Discussionsupporting
confidence: 80%
“…Finally, intestinal HCO 3 − secretion results in formation and excretion of CaCO 3 by marine fish which amounts to at least 3–15% of the marine inorganic CaCO 3 production 24 . Although a study on the toadfish reported unaltered CaCO 3 excretion rates 22 at 1900 μatm a more recent study on toadfish 23 and an earlier study on midshipmen 46 may suggest otherwise. Thus, increased intestinal HCO 3 − loss at elevated CO 2 in other species may impact the magnitude of this globally important calcification process, a possibility worthy of further study.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In part, changes could relate to rising levels of atmospheric CO 2 and subsequent elevations in surface seawater temperatures and pCO 2 , both of which are predicted to stimulate increased carbonate production rates at the level of individual fish 1 , albeit effects remain to be fully quantified 45 . Such a response would contrast with that predicted for many other calcifying organisms under elevated pCO 2 46 , and it is possible that fish will contribute an increasingly large proportion of total marine carbonate under future climate change scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Tank floor recovery is a widely adopted approach to sampling piscine gut carbonates 8, 1214, 22, 45 but other methods include direct sampling from the intestinal tract (following animal euthanasia) 8, 22, 45 and collection in a surgically attached rectal sac 45 . Direct sampling from the intestine was unsuitable here for two reasons.…”
Section: Methodsmentioning
confidence: 99%